Pengaruh Hambatan Samping Terhadap Kapasitas Dan Kinerja Jalan Pada Kota Makassar (Studi Kasus : Jalan Andalas) - Constantinus Ricky P Rukka; Mary Selintung; Louise Elizabeth Radjawane (Paulus Civil Engineering Journal, 2023)
However, along with the pace of population growth and progress in the world of transportation, various problems have appeared. Currently, the problem of traffic congestion has been troubling for road users and has become a widespread problem. This also happened on Jalan Andalas which is the main access road. This study aims to determine the performance of road sections and the impact of side obstacles on the capacity of Andalas Road sections. Data collection is divided into primary data obtained from surveys at the location, namely data on traffic volume, side friction, vehicle speed and road geometry as well as secondary data, namely population data, in data processing using the Indonesian Road Capacity Manual 1997 (MKJI 1997) Urban roads. Based on calculations and analysis of data for 7 days of observation, the largest traffic flow was obtained on Tuesday, namely 1,941.8 pce/hour, the highest side resistance on Tuesday with a total of two directions during the average peak hour flow, namely 342.9 events/hour and the highest degree of saturation is 0.394. The effect of side friction on road capacity is that the greater the side resistance, the lower the capacity and performance of the road segment, conversely if the side resistance is low, the load capacity is large.